Exploration of Leadership, Organizational Culture, Job Satisfaction, and Employee Performance - Purwadi; Dio Caisar Darma; Widya Febrianti; Dedy Mirwansyah (Technium Social Sciences Journal, 2020)
The purpose of the organization is to obtain maximum results and also pay attention to performance in the process of these objectives. The description of the research aims to explore the relationship between leadership and organizational culture on job satisfaction and employee performance. The independent variables of this research are leadership and organizational culture. Meanwhile, job satisfaction and performance are included in the dependent variable. This research was conducted at the Department of Transportation (Samarinda City) consisting of 83 respondents. Research is descriptive and quantitative. Data collection by questionnaire by testing the leadership and organizational culture on performance and moderated by the variable job satisfaction. Data analysis uses the Partial Least Square (PLS) technique. Empirical findings indicate that leadership and organizational culture have a positive and significant effect on job satisfaction. Leadership and organizational culture have a positive and significant impact on performance. On one hand, the results of the study also showed that job satisfaction had a negative and not significant effect on performance. Researchers who have a focus on the variables in this study, in order to be able to use the criteria for selecting more respondents and more detailed in the future.